An Intramedullary Osteolipoma of the Upper Thoracic Spinal Cord: A Case Report. Issue 3 (July 2016) - Kojima, Kota; Iwanami, Akio; Mikami, Shuji; Ishii, Ken; Matsumoto, Morio; Nakamura, Masaya
Abstract : Case: We present a rare case of an intramedullary osteolipoma without any extramedullary connections or coexisting spinal dysraphism. A 48-year-old woman presented with back pain and pain around the lateral aspect of the left thigh. Magnetic resonance imaging (MRI) revealed a heterogeneous hyperintense and hypointense region on T1 and T2-weighted imaging. A cavernous hemangioma was suspected, and the patient was admitted for surgical resection. The histological diagnosis was an intramedullary osteolipoma. Conclusion: MRI with fat suppression and computed tomography are recommended for the diagnosis of an intramedullary osteolipoma, but a definitive diagnosis requires histological examination.